Implementasi penggunaan media lagu untuk meningkatkan kemampuan kognitif siswa dalam pembelajaran IPA kelas IV sekolah dasar negeri pace 03 kecamatan silo - Juhari, khoiriyaputri (Jurnal Pendidikan Biologi Undiksha, 2023)
Students' cognitive development must be considered during the learning process, the use of learning media can make it easier for students to receive learning so they can achieve learning goals. The use of song media is one of the media sources that can be used to convey material to students. The aim of this research is to find out how to implement the use of song media to improve students' cognitive abilities in class IV science learning at state elementary school 03 Pace Slo. This research uses qualitative methods, using observation data collection techniques and interviews with the class IV homeroom teacher at SDN 03 Pace Silo. Based on the research results, the use of the song method is very effective for use in grade IV science learning. Research shows that the use of song media can improve students' cognitive abilities, whether they realize it or not. The use of song media makes students active and enthusiastic about learning compared to monotonous and boring learning for students.